Prevalence of Diabetes Mellitus Comorbidity in COVID-19 Patients Treated at Selected Hospital in Surabaya - Mustafida, Nurida Alfi; Diyantoro; Sundari, Aliyah Siti; Indriati, Dwi Wahyu (International Journal of Scientific Research in Biological Sciences, 2022)
COVID-19 or commonly called Coronavirus disease 2019 by the World Health Organization (WHO) is a new virus that is currently troubling people in all parts of the world and having a very significant impact on human life, especially in the health sector. COVID-19 is an infectious disease caused by the acute respiratory syndrome coronavirus. Diabetes Mellitus (DM) is one of the risk factors for increasing the severity of COVID-19 infection. Older patients (>60 years), uncontrolled blood sugar levels, and the presence of diabetic complications are associated with a poorer COVID-19 prognosis. This study aims to determine the prevalence of comorbid diabetes mellitus in COVID-19 positive patients at selected hospital in Surabaya in 2020. This study used the Observational Analytic Cross-sectional method using secondary data from records of blood sugar examination results in the clinical pathology laboratory at at selected hospital in Surabaya in 2020. Data in the form of positive COVID-19 patients who were confirmed with PCR test results in 2020. The results of the study obtained data as many as 151 positive COVID-19 patients who underwent blood sugar checks, with a history of diabetes mellitus as much as 29.9% and the majority group aged 56-65 years, namely as much as 42.2% can be seen from the gender where women are more vulnerable that is equal to 64.4%. Both COVID-19 patients and DM patients are expected to better manage themselves to avoid complications.